USING TEACHING / LEARNING AIDS IN THE TEACHING OF PRIMARY SCHOOL SUBJECTS IN BINGA DISTRICT - NDLOVU, FRANCIS (IJRDO- Journal of Educational Research, 2017)
The aim of the present study is to investigate whether teachers in primary schools in Bingadistrict effectively use audio-visual aids when delivering lessons for social studies. Thepopulation comprised of all the 1200 teachers in the primary schools and a sample of 320randomly selected teachers was used. The study employed the quantitative methodology andadopted the descriptive survey design. All the data was gathered by use of a questionnaire whichlargely had close-ended questions and two open-ended ones. The study revealed that teacherswere not effectively using audio-visual aids to deliver lessons. The study recommends thatschool heads should motivate teachers and guide them in the use of teaching / learning aids forall subject areas. The Ministry of Primary and Secondary Education is also implored toresuscitate the Audio-Visual Services Unit in order for schools to procure instructional materialsfrom the unit.